Strategy of geothermal energy development as a renewable energy source in West Java Indonesia - Fauzia, Assyifa; Makarim, Muhammad Nabil (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2024)
Background: Indonesia has vast renewable energy potential, including biofuels, biomass, and bioenergy from tropical biodiversity spread across the country. Hydropower and geothermal energy are the only forms of renewable energy used to generate electricity and are connected to the grid. Geothermal energy may be incorporated into the grid to create hybrid energy systems that will help to reduce the high energy demand while maintaining low energy costs and net present costs. There are now 14 biosphere reserves in Indonesia, divided into 24 units of core zones, six units of buffer zones, and 13 units of transition zones. The West Java Province has a geothermal potential of 6,101 MWe or 21% of Indonesia's total geothermal resources. Currently, the installed capacity of electricity from geothermal energy in West Java is 1075 MWe or 89% of the total national installed capacity of 1196 MWe. Method: This paper reviews West Java Province data collection from official government bureaus, state-owned businesses, and non-governmental organizations (NGO) reports on geothermal energy capacity, electricity installation, and used area of ​​geothermal power plant and will be limited to the years 2010 through 2020. The collected data will then be refined, extrapolated, and analyzed by the connected trend to aid in studying West Java geothermal growth and use SWOT method analysis. Finding: The result of this research is a strategy for optimizing the development of geothermal energy utilization. The strategies that can be developed are infrastructure improvement as an investment facilitation strategy, a strategy to leverage a costly investment and capital investment, underground mining in conservation forest areas to avoid degradation improvement and supervision of related institutions and stakeholders, implementation of environmentally sustainable development, and socializing programs and providing job opportunities for the local community. Conclusion: Indonesia has an enormous potential for renewable energy, especially geothermal, with West Java Province having the largest installed capacity. This study suggests strategies to optimize geothermal energy development, including improving infrastructure, investment facilities, underground mining, improving supervision, and sustainable development. Novelty/Originality of this study: Research on geothermal energy in West Java provides a comprehensive analysis and specific strategies to optimize the development of this energy in the area, including innovative underground mining approaches.